The Impact of Influencer Affecting Community Products Purchase Decision Making via TikTok Application - Pislae-ngam, Kattakamon (Journal of Humanities and Social Sciences Thonburi University, 2024)
The objective of this research ware to 1) study the differentiate demographic factors on community purchasing decisions on the TikTok application and 2) study the influence of influencers on community purchasing decisions on the TikTok application. The samples were 400 people from experienced community purchasers through the TikTok application. Selected by convenient random method. Data were collected using questionnaires. The analysis data was using descriptive statistics, including frequency, percentage, average, and standard deviation. Statistical hypothesis analysis used t-test, One-way ANOVA and Multiple Regression Analysis. The results showed that demographic factors influenced community purchase decisions on the TikTok application. There were females, marital status, age between 31–40 years old, having the bachelor’s degree of education; most of them are employee in private companies which have an amount of 20,001 – 30,000 bath income. The level of influence factor of community products purchasing decision was at a high level. The hypothesis test results showed that the results of the hypothesis test showed that 1) the demographic aspect of gender had a significant difference of 0.05 and 2) influencers’ influence on community purchase decisions on TikTok applications included trustworthiness, expertise, and similarity with the target audience. Impact on community purchase decisions on the TikTok application is statistically significant at the level of 0.05, 71.6 percent have forecasting power. This can be written as an equation as follows: Y = 1.121 + 0.435(X5) + 0.423(X2) + 0.317(X1)